2015
DOI: 10.1177/0146167215594591
|View full text |Cite
|
Sign up to set email alerts
|

Some “Thing” to Talk About? Differential Story Utility From Experiential and Material Purchases

Abstract: Psychological research has shown that experiential purchases (a hike in the woods, a trip to Rome) bring more happiness than material purchases (a designer shirt, a flat-screen television). The research presented in this article investigates one cause and consequence of this difference: People talk more about their experiences than their possessions and derive more value from doing so. A series of eight studies demonstrate that taking away the ability to talk about experiences (but not material goods) would di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 45 publications
8
125
1
1
Order By: Relevance
“…Participants in Study 1a were told to imagine that they were given $1500 to spend on two purchases: an electronic gadget that cost $750 and an all‐expenses‐paid beach vacation that also cost $750. It is worth noting that in addition to being matched on price, these two broad categories have been shown in previous research (Kumar & Gilovich, in press) to be comparable in subjective appeal. That is, 40 raters in a separate investigation (from the same participant pool) confirmed that vacations and electronic goods are seen as roughly equally attractive.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Participants in Study 1a were told to imagine that they were given $1500 to spend on two purchases: an electronic gadget that cost $750 and an all‐expenses‐paid beach vacation that also cost $750. It is worth noting that in addition to being matched on price, these two broad categories have been shown in previous research (Kumar & Gilovich, in press) to be comparable in subjective appeal. That is, 40 raters in a separate investigation (from the same participant pool) confirmed that vacations and electronic goods are seen as roughly equally attractive.…”
Section: Methodsmentioning
confidence: 74%
“…Because people consume anticipation and get more utility from waiting for experiences than waiting for possessions (Kumar & Gilovich, in press; Kumar et al, 2014; Loewenstein, 1987), we examined whether people are more inclined to delay the consumption of experiences than the consumption of material goods. More specifically, would people prefer to have a possession now and an experience later, or an experience now and a possession later?…”
Section: Experiments 1a–1cmentioning
confidence: 99%
“…Epicuro entendia que, para sermos felizes, temos de nos afastar das distrações do mundo comercial, gozar o máximo a vida, cercando-nos de amigos e sem desejar o que não precisamos, sem consumismo, e procurando priorizar a qualidade e não a quantidade do que é vivido. O confronto entre quantidade e qualidade é observado em estudos de Gilovich et al (2015a;2015b) que comparam o prazer obtido em compras materiais e em compras experienciais.…”
Section: Afinal 'Onde Está a Felicidade?'unclassified
“…Telling the story of an enjoyable past experience also enhances experience duration estimation (Vilches-Montero and Spence 2015) and the self (Chawdhary and Riley 2015). Value derived from talking about experiences (Kumar and Gilovich 2015) and retrospective dilution of the most extremely negative moment in a positive experience (Cowley 2014) explain these amplifications. The previously mentioned articles measure the effects of WOM on storytellers in a western context.…”
Section: Introductionmentioning
confidence: 99%